Step 4...This yields x^2+(b/a)x=-c/a

Step 5...Add the square of half of the coefficient of b/a to both sides of the equation

Step 6...This yields x^2+(b/a)x+(1/2 of b/a)^2=-c/a+(1/2 of b/a)^2....equ(2)

Step 7...This yields x^2+(b/a)x+(b/2a)^2=-c/a+(b/2a)^2...equ(3

Step 8... Combining the L.H.S of equation 3 in the form of (x+b/2a)2=-c/a+b^2/4a^2Step 9...Evaluating the R.H.S (x+b/2a)^2=b^2-4ac/4a^2 Step 10...Take the square root of both sides..this yields x+b/2a=+ or-✓b^2-4ac/4a^2

Step 11...this yields x+b/2a=+ or - ✓b^2-4ac/✓4a^2

Step 12..this yields x+b/2a=+ or -✓b^2-4ac/2a

Step 13...Take b/2a to the R.H.S

2.Algebraic Formula

Mathematics was first discovered among the greeks.Earlier since then mathematics became a subject that no one can do without